Preventive effects of taurine against d -galactose-induced cognitive dysfunction and brain damage - Tu, Dom-Gene; Chang, Yao-Ling; Chou, Chung-Hsi; Lin, Yi-Ling; Chiang, Chia-Chun; Chang, Yuan-Yen; Chen, Yi-Chen (Food & function, 2018)
Oxidative stress arising from life processes or environmental influences and its resultant cellular dysfunctions are major causes of neurodegenerative disorders. The objectives of this study were to investigate whether taurine (Tau) can prevent d -galactose-induced cognitive dysfunction and brain oxidative damage. Mice given with Tau supplementation (100 and 400 mg per kg BW per day) spent shorter ( p < 0.05) time in searching target in d -galactose (100 mg per kg BW per day) treated mice in a water maze reference memory experiment. Moreover, Tau supplementation extended ( p < 0.05) the searching period around the target quadrant in the probe test of the water maze, and neuronal degeneration and nucleus shrinkage in the hippocampus dentate gyrus area of d -galactose treated mice were observed to be attenuated. Tau also downregulated ( p < 0.05) expression of the glial fibrillary acidic protein ( Gfap ) and of the cluster of differentiation marker Cd11b ; meanwhile, it strengthened ( p < 0.05) antioxidant capacity and lowered ( p < 0.05) the accumulation of advanced glycation end-products (AGEs) in the brain. Therefore, Tau could be effective to ameliorate oxidative damage and inflammation in the brain, and apoptosis of brain cells, which further lessen the cognitive dysfunction.